Study about Hydrophilic Modification of PTFE Membrane (Journal of Fiber Bioengineering and Informatics, 2019)
Polytetrafluoroethylene (PTFE) membrane is widely used in medicine, clothing, chemical, electronicsand other fields. However, due to the highly symmetrical structure of the PTFE, the absence of reactiveradical, high crystallinity, low surface energy and poor surface wetting, these properties of PTFE affectits compound with other materials. In order to improve the adhesion property of PTEF membrane, thesurface must be modified. In this paper, the surface melting deposition method was used to improve thehydrophilicity of PTFE membrane. The PTFE membrane is immersed in a suspension of nano-TiO2, andthen deposited by melting at a high temperature. Sintering and depositing TiO2 particles on the surfaceof the PTFE membrane. The molecules of the viscous substance enter the surface layer of the PTFEmembrane to form a modified surface layer. The interface strength of PTFE membrane is increased,and the surface activity of PTEF membrane is increased, and the hydrophilicity of the PTFE membraneis improved. It is easier that PTFE membrane is combined with other materials. The best treatmentprocess for the modification by melting deposition is as follows: the optimum treatment temperature is350◦C, and the optimum treatment time is 30 min.